Disease severity and mean platelet volume in elderly patients with pulmonary embolism - Grzegorz Staśkiewicz; Piotr Piech; Elżbieta Siek; Sebastian Uhlig; Magdalena Zakościelna; Joanna Kurzepa; Piotr Przybylski; Jacek Baj; Jerzy Przegaliński; Elżbieta Czekajska-Chehab; Andrzej Drop (Kazimierz Wielki University, 2017)
Elderly patients are at higher risk of venous thromboembolism, including pulmonary embolism. Furhtermore, clinical course is frequently more servere. Platelet parameters are of increasing interest in thrombosis research, including mean platelet volume, which is a recognized indicator of increased thrombotic activity. The aim of the study was to compare severity of pulmonary embolism as measured by computed tomography, as well as mean platelet volume in younger and elderly patients. Retrospective analysis of 150 patients data was performed. Both younger and older patients presented with similar pulmonary embolism severity, time since onset of symptoms, as well as d-dimer levels. Elderly patients, however presented with significantly wider pulmonary artery diameter and larger mean platelet volume were observed. In older patients group, even at the same severity of PE, significant differences of both CT-derived and platelet parameters are present.